PENGARUH AUDIT TENURE DAN PERGANTIAN AUDITOR TERHADAP AUDIT DELAY (Studi Kasus pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017) - Kristanti Rahman; Iva Nur Afifah (JURNAL EKONOMI, 2019)
The accuracy of the company to publish finansial statements may delay experience caused by the length of the auditors in completing its audit work. Auditors perfom the audit tasks based on a Public Accountant Professional Standards (SPAP). Financial statements are very important for the company in making decisions and therefore the auditor must complete the audit on time. The study aims to knowing influencing of Audit Tenure (X1) and Auditor Turnover (X2) on Audit Delay (Y) and to knowing influencing of Audit Tenure (X1) and Auditor Turnover (X2) together on audit delay (Y). Data used in this reasearch are Manufacturing Business data in Basic Industry and Chemical Sectors on the Indonesian Stock Exchange (IDX) 2014-2017. The period of this research is for 4 years, started from 2014 until 2017 for was data of Manufacturing Business in Basic Industry and Chemical sectors on Indonesian Stock Exchange. The sampel selected by purposive sampling method. The type of data used is secondary data and total sample used in this research is 54 companies that have been selected based on predetermined criteria. Methods of data analysis used is multiple linear regression. The results of this research indicate that : 1. Audit tenure doesn’t affect audit delay. 2. Auditor turnover affects audit delay. 3. Audit tenure and auditor affects audit delay. Further research is recommended that can expand the research sample, add variables and extend the periodde of research. Keywords : Audit Tenure, Auditor Turnover, and Audit Delay.